Students’ Creative Thinking Process in Solving Open-Ended Problems on Flat Shapes - Devi Nur Afifah; Sudirman Sudirman; Swasono Rahardjo (Universitas Suryakancana, 2025)
Creative thinking is crucial in mathematics education, particularly when students are required to solve open-ended geometry problems that allow multiple solution strategies. However, few studies have examined how students’ creative thinking processes occur when solving open-ended problems on flat shapes, especially based on Wallas’ four-stage model. This study aims to describe students’ creative thinking processes in solving open-ended tasks on flat shapes through the stages of preparation, incubation, illumination, and verification. A descriptive qualitative approach was employed. From 32 junior high school students, three were selected purposively to represent high, moderate, and low levels of creativity. Data were collected through creative-thinking tasks and interviews, and analyzed using the Miles and Huberman model. The findings show clear differences in thinking patterns: highly creative students successfully performed all four stages and generated accurate and varied solutions; moderately creative students experienced difficulties during illumination, particularly in selecting correct formulas and understanding composite shapes; while low-creative students struggled from the preparation stage, indicating difficulty comprehending the problem and applying concepts. This study contributes to understanding how creative thinking develops across different ability levels and highlights the importance of learning strategies that support each stage of the creative thinking process. The results imply that open-ended tasks in geometry can be optimized to foster creative mathematical thinking when accompanied by appropriate guidance.